Method and apparatus for producing nanometer-scale particles for energy storage materials - Patents.com
By employing electrostatically stabilized slurries with electrostatic stereodispersants in media mills, the challenges of particle aggregation and energy inefficiency in producing submicron particles are addressed, resulting in high-quality nanometer-scale particles for energy storage materials.
Patent Information
- Application Number
- JP2024554741
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-15
- Filing Date
- 2023-03-15
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Conventional methods for producing submicron particles using wet milling face challenges such as particle aggregation, increased viscosity, and energy inefficiency, which hinder the production of high-quality energy storage materials like battery precursors.
The use of electrostatically stabilized slurries in media mills, specifically with the addition of electrostatic stereodispersants like polyelectrolytes, helps maintain particle separation and prevents aggregation, thereby enabling the production of nanometer-scale particles with improved milling efficiency and reduced energy consumption.
This approach effectively generates nanometer-scale particles with controlled size distribution, reducing aggregation and viscosity issues, and enhancing the production of high-quality energy storage materials suitable for industrial-scale manufacturing.
Smart Images

Figure 2025509542000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims priority to U.S. Patent Application No. 17 / 654,915, filed March 15, 2022, which is incorporated by reference in its entirety herein.
[0002] The present disclosure relates generally to methods and apparatus for producing ultrafine particles for various industrial and commercial purposes, including the fabrication of energy storage materials and / or devices. More specifically, the present disclosure relates to methods and apparatus for producing nanometer-scale particles utilizing electrosterically stabilized slurries in media mills, such as ball mills, planetary mills, conical mills, and stirred media mills. The nanometer-scale particles can be used to produce energy storage materials, such as battery precursors for use in electrodes and / or separators for batteries and capacitors. [Background technology]
[0003] Media milling generally refers to the process of breaking down relatively large sized particles of media to relatively small sizes through the application of mechanical action. Traditional milling methods include dry milling and wet milling. In dry milling, air (or an inert gas) is used to keep the particles in suspension while the mechanical action is applied to the particles. However, as the particle size is reduced, the fine particles tend to aggregate in response to van der Waals forces, which limits the capabilities of dry milling. In contrast, wet milling uses liquids such as water and organic solvents such as alcohols, aldehydes, and ketones to control the re-agglomeration of the fine particles. Thus, typically, wet milling is used for the subdivision of submicron sized particles. Another process for making submicron particles is jet milling. It is a dry process that uses supersonic air or supersonic streams. However, jet milling is very costly as it is highly energy intensive.
[0004] In conventional practice, wet mills typically include milling media that, when subjected to mechanical action such as stirring or agitation, impart sufficient force to break up particles suspended in a liquid medium. Milling devices are classified by the method used to impart said mechanical action to said media. The action imparted in a wet mill can include, among others, stirring, tumbling, vibratory motion, planetary motion, agitation, and ultrasonic milling.
[0005] Of the above mill types, the stirred media mill, which utilizes balls of various sizes as its milling media and agitation as its method of imparting mechanical action, has several advantages for particle refinement, including high energy efficiency, high solids handling, production of products with narrow size distributions, and the ability to produce homogeneous slurries. Variables that may be considered when using a stirred media mill include, for example, agitator speed, suspension flow rate, residence time, slurry viscosity and concentration, solid size of the particles being fed, size of the milling media (i.e., balls), media packing (i.e., amount of beads in the mill chamber), and desired product size.
[0006] However, despite these advantages, stirred media mills have some drawbacks when the desired product particle size falls below about 1 micrometer, especially below about 500 nanometers. For example, in the submicron particle size range, the behavior of the product suspension (slurry) becomes increasingly influenced by particle-particle interactions. These interactions may cause natural aggregation of particles, increasing the viscosity of the product suspension. When the product particle size falls below about 1 micrometer, these interactions may reach an equilibrium state between aggregation, deagglomeration, and fragmentation, and increasing energy input may not result in further fragmentation. Furthermore, particle aggregation, along with the increase in viscosity of the product suspension, increases the required power consumption due to higher loads on the motor mill, but may also block the media mill screen, preventing further flow of the suspension and preventing particles from being discharged as product from the mill.
[0007] Various methods have been attempted to suppress these reagglomeration effects. For example, electrostatic stabilization methods have been used to maintain particle separation during milling. As shown in Figure 1, electrostatic stabilization creates similar charges on the surfaces of colloidal particles so that they repel each other, thereby dispersing the suspension of the particles. Electrostatic stabilization methods can be performed by adjusting the pH of the product suspension. Adjustment of the pH can be controlled by the addition of either acids or bases, including weak and strong acids and weak and strong bases. Alternatively, electrostatic stabilization methods can be performed by adding anionic or cationic dispersing agents to the product suspension. These dispersing agents electrostatically stabilize the product suspension by adding positive or negative charges to the particles when the dispersing agent is adsorbed to the surface of the particles.
[0008] However, these electrostatic methods have several drawbacks that make them difficult to implement in industrial-scale production. In particular, electrostatic methods require constant monitoring and adjustment of the process, since as particle size decreases, their surface area increases and any added acid / base or dispersant becomes less effective. As the surface area of the particles increases exponentially and the particle size decreases, more and more acid, alkali, or dispersant is required, and if the amount deviates even slightly from the required amount, the entire suspension becomes prone to flocculation and further milling becomes impossible due to a sudden increase in viscosity and blockage of the mill screen.
[0009] In another example, steric stabilization methods are used to maintain particle separation during milling. Steric stabilization methods utilize non-ionic or neutral dispersants to separate the particles in suspension. As shown in Figure 2, steric stabilization involves adsorbing relatively long chain polymeric compounds to the surface of the particles. Some of the polymers adhere strongly to the surface of the particles, while the rest of the polymers are free to dangle in the liquid medium of the suspension. If the liquid medium is a good solvent for the polymers, interpenetration of polymer chains, i.e., interaction between polymers on separate particles, is energetically unfavorable. As a result, individual particles repel each other (interparticle repulsion), which disperses the suspension.
[0010] However, like the electrostatic methods, these steric methods have several drawbacks that make them difficult to implement in industrial-scale production. For example, sterically stabilizing dispersants have the disadvantage that larger amounts of dispersant are required as smaller and smaller particle sizes are produced. During milling, the surface area of the particles increases exponentially, reducing the adsorption of these dispersants on the surface of the particles and making the milling process difficult to control.
[0011] One area of increasing interest in processes that can realize the benefits of nanometer-scale particles is energy storage materials and energy storage systems. There is a great deal of effort being made to develop cost-effective renewable energy sources for energy storage, such as batteries, to store power during excess generation and supply it during peak demand. In this regard, it is essential to develop low-cost, scalable energy storage systems with reasonable cycle life and safety. In addition, increasing energy density without compromising safety is also important for some applications, such as electric vehicles and consumer electronics such as mobile phones and laptops.
[0012] It is known that for nanometer-scale particles and energy storage materials (e.g., for batteries), certain material factors can have a significant impact on performance. For example, increasing the surface area of the electrode leads to improved efficiency of electrochemical reactions and promotes ion exchange between the electrode and the electrolyte, especially in the negative electrode. This is because the larger the surface area, the shorter the diffusion path for lithium ions between the negative electrode particles. However, the larger the surface area, the more limitations there are due to the deterioration of electrolyte interactions at the surface of the electrode, resulting in loss of capacity and thermal stability. Thus, nanoparticles hold great promise for increasing the surface area without such capacity loss, which can facilitate fast charging, efficient discharging, and increased capacity of batteries.
[0013] The size, shape, and tortuosity of the electrode pores also significantly affect the ion (e.g., lithium ion) transport rate through the electrolyte held within the porous structure of the electrode. The microstructure of the electrode as a result of the manufacturing process directly impacts the energy density, power, lifetime, and reliability of lithium-ion cells. Thus, a better understanding of the interconnectivity of adjacent pores, closed pores, and channels that may be created during the manufacturing process helps ensure optimal electrolyte-electrode interactions. Knowledge of the tortuosity of the porous electrode-electrolyte interface allows one to determine whether cell performance limitations are due to the microstructure.
[0014] Other physical properties also have a significant effect. For example, particle shape affects properties such as packing density, since spherical particles can be packed more densely than fibrous or flake-shaped particles. The density of an electrode, such as a graphite anode, affects its ability to withstand degradation under difficult load and discharge operations. Increasing the density of electrode particles in the anode reduces the porosity, resulting in a reduction in the effective surface area of the electrode. This reduces the contact area between the electrode and the electrolyte. Similarly, the porous structure of the electrode has a direct effect on the particle-particle contact between the active material and the conductive diluent. Controlling the porosity can increase the conductivity in the electrode for proper electron exchange, while ensuring sufficient voids for electrolyte access and (for example) lithium ion transport for positive electrode intercalation. Conversely, void blockage (clogging) during intercalation can reduce capacity.
[0015] Not only chemical composition affects the electrochemical properties of electrode materials. To obtain the best performance from the cathode materials, particle size and morphology must also be considered. In addition, successful lithiation is the most important factor that determines the capacity of the cathode materials. Different physical properties such as particle size and porosity of the precursors result in different requirements for lithiation time and temperature. The particle size distribution as well as porosity also affect the final capacity and cycling stability.
[0016] The particle size of the electrode material is also important, as it affects the capacity, cycling, and coulombic efficiency. The particle size influences the amount of solid-state diffusion of intercalating lithium ions in the electrode. Smaller particles, especially for nanoparticles, result in smaller volume changes with cycling. This contributes to reduced mechanical loads, increased hardness, and improved resistance to fracture. Interestingly, it has been reported that a broad particle size distribution may enable higher energy density compared to a monodisperse distribution. Thus, controlling and customizing the particle size distribution allows for individual fine-tuning, which results in high power (monodisperse) or high energy density (polydisperse) materials.
[0017] One application that could benefit from such regulation and control is the production of lithium-ion batteries. Advantages of nanomaterials specifically relevant to lithium-ion battery applications include: (i) New reactions are obtained that cannot occur with micrometer-sized particles (e.g., when transition metal compounds react with Li, metal nanoparticles embedded in a Li2X matrix are formed in situ, where X is O, S, F, or N)). (ii) Nanostructured materials offer shorter path lengths for both Li+-ion diffusion and electron transport compared to micrometer particles, thus enabling improved charge / discharge rates. (iii) The short path length for electron transport allows the use of materials with low electronic conductivity. (iv) The increased contact area between the electrode and the electrolyte can also improve the charge / discharge rate. (v) The nanomaterials can accommodate the large volume expansion / contraction associated with Li+-ion transport and preserve the integrity of the electrodes, thereby extending the cycle life. Unfortunately, despite these promising effects, there are some drawbacks, including: (i) The large surface area can increase undesired reactions between the electrodes and the electrolyte, resulting in the formation of a solid electrolyte interface (SEI), which can lead to cell self-discharge, poor cyclability, reduced calendar life, and reduced safety. (ii) The packing of particles is poor.
[0018] It is therefore desirable to provide an improved method for producing particles in the submicron range using a wet milling process that advantageously maintains particle separation when particle sizes are below 1 micrometer to avoid agglomeration and mill screen blockage. Moreover, the wet milling process is advantageously suited for industrial-scale production in that extremely strict control of any additives is not required to prevent flocculation or viscosity spikes in the product suspension. Such an improved method, when used with certain precursor materials suitable for use in energy storage devices, can advantageously provide submicron particulate materials useful for preparing improved energy storage materials, such as electrodes and separators for batteries and supercapacitors. Additionally, other desirable features and characteristics of the isolator assembly will become apparent from the following detailed description and appended claims, taken in conjunction with the accompanying drawings and the foregoing background. Summary of the Invention
[0019] Disclosed herein is a method and apparatus for producing nanometer-scale particles utilizing electrosterically stabilized slurries in a media mill. According to one embodiment, a method for producing nanometer-scale particles includes adding a feed substrate suspension to a media mill. The feed substrate suspension includes a liquid carrier medium and feed substrate particles. The method further includes adding an electrosteric dispersant to the feed substrate suspension in the media mill. The electrosteric dispersant includes a polyelectrolyte, various examples of which are listed in more detail below. Still further, the method includes operating the media mill for a period of time to break down the feed substrate particles, thereby forming nanometer-scale particles having a size of less than about 1 micron (D 90 ) particle size and recycling the nanometer-scale particles from the media mill for further grinding.
[0020] According to another embodiment, a media mill apparatus configured to produce nanometer-scale particles includes a milling chamber, an agitator extending into the milling chamber, milling media disposed within the milling chamber, and a feed substrate suspension including a liquid carrier medium and feed substrate particles, the feed substrate suspension being disposed within the milling chamber and interspersed with the milling media. The media mill apparatus further includes an electrostatic steric dispersant including a polyelectrolyte mixed within the feed substrate suspension. The agitator applies a mechanical action to the milling media for a predetermined period of time, thereby causing the milling media to break down the feed substrate particles to particles of less than about 1 micrometer (D 90 ) particle size.
[0021] According to yet another embodiment, a method for forming nanometer-scale particles in a media mill containing milling media is provided, the method comprising adding a feed substrate suspension to the media mill. The feed substrate suspension comprises a liquid carrier medium comprising water or an organic solvent, and feed substrate particles comprising any solid material that needs to be milled to a small size, such as glass, graphene, metals, minerals, ores, silica, diatomaceous earth, clay, organic and inorganic pigments, pharmaceutical materials, or organic or inorganic solids such as carbon black. The feed substrate particles are present in the feed substrate suspension in an amount of about 5% to about 70% by weight, or about 5% to about 40% by weight of the feed substrate suspension. The method further comprises adding an electrostatic steric dispersant to the feed substrate suspension in the media mill. The electrostatic steric dispersant comprises a polyelectrolyte. The polyelectrolyte comprises a polymer or copolymer having a charged functional group or an inorganic affinity group. The electrostatic steric dispersant is added in an amount of about 2% to about 20% by weight of the feed substrate particles. The method further comprises operating the media mill for a time period of about 10 minutes to about 6,000 minutes to break down the feed substrate particles to a size of less than about 1 micron (D 90 forming nanometer-scale particles having a particle size of 1000 to 2000 nm, and recycling the nanometer-scale particles from the media mill for further grinding and separating the nanometer-scale particles from the milling media. Still further, the method includes drying the nanometer-scale particles after separating the nanometer-scale particles from the milling media.
[0022] In an additional embodiment, a method for preparing nanometer-scale particles for an electrochemical material is provided. The method includes adding a feed substrate suspension to a media mill. The feed substrate suspension includes a liquid carrier medium and electrochemical feed substrate particles. The method further includes adding an electrostatic steric dispersant to the feed substrate suspension in the media mill. The electrostatic steric dispersant includes a polyelectrolyte, various examples of which are listed in more detail below. Still further, the method includes operating the media mill for a predetermined time to break down the feed substrate particles, thereby forming nanometer-scale particles of less than about 1 micrometer (D 90 and recycling the nanometer-scale particles from the media mill for further grinding. The method optionally includes, after separating the nanometer-scale particles from the milling media, drying the nanometer-scale particles, such as by spray drying. In some embodiments, recycling and further grinding the nanometer-scale particles from the media mill forms a slurry, and the method includes directly spray drying the slurry to obtain the nanometer-scale particles as a dry powder.
[0023] This Summary is provided to introduce a selection of concepts in a simplified form that are further described below in the Detailed Description. This Summary is not intended to identify key features or essential features of the claimed subject matter, nor is it intended to be used as an aid in determining the scope of the claimed subject matter. [Brief description of the drawings]
[0024] The present disclosure will now be described in conjunction with the following figures, in which like numbers refer to like elements and in which: [Figure 1] FIG. 1 is a schematic diagram illustrating particle separation of a product suspension using electrostatic methods as practiced in the prior art. [Diagram 2] FIG. 1 is a schematic diagram illustrating particle separation of a product suspension using a steric method as practiced in the prior art. [Diagram 3] 3A-3B are schematic diagrams of a wet media mill useful for milling particles in a continuous process according to some embodiments of the present disclosure. [Figure 4] FIG. 1 is a schematic diagram illustrating particle separation of a product suspension utilizing electrosteric methods in accordance with some embodiments of the present disclosure. [Diagram 5] 1 is a flow chart illustrating a method for wet media milling in accordance with some embodiments of the present disclosure. [Figure 6] 6A-6E are graphs illustrating average particle sizes of particles produced according to some embodiments of the present disclosure. [Figure 7] 1 is a flow chart illustrating a method of preparing an energy storage material by wet media milling and spray drying according to some embodiments of the present disclosure. [Figure 8] 8A-8B are scanning electron microscope (SEM) micrographs of the feed materials utilized in the examples. [Figure 9] 1 is a SEM micrograph of the aggregates of primary nanoparticles prepared in the examples after spray drying. [Figure 10] 10A-10E are SEM micrographs of the spray-dried aggregates prepared in the examples, showing the various appearances of the primary nanoparticles contained therein. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] The following detailed description is merely exemplary in nature and is not intended to limit the invention or the application and uses of the invention. As used herein, the term "exemplary" means "serving as an example, instance, or illustration." Thus, any embodiment described herein as "exemplary" should not necessarily be construed as preferred or advantageous over other embodiments. Moreover, as used herein, ordinal numbers such as "first," "second," and "third," such as first, second, and third components, only refer to different units of multiple items, unless otherwise specified by the appended claims. All embodiments and implementations described herein are exemplary embodiments provided to enable one of ordinary skill in the art to make or use the invention, but not to limit the scope of the invention, which is defined by the claims. Furthermore, there is no intention to be bound by any expressed or implied theory presented in the preceding technical field, background, brief summary, or the following detailed description.
[0026] Disclosed herein are embodiments of a method and apparatus for producing nanometer-scale particles using electrostatically stabilized slurries in a media mill. The disclosed embodiments utilize electrostatic steric (electrostatic and steric) stabilization of ultrafine (submicron) particles in a wet milling process using electrostatic steric dispersants. Electrostatic steric dispersants are polymers that can electrostatically and sterically stabilize product particle suspensions. The use of electrostatic steric dispersants reduces the use of the dispersant, the amount of dispersant used needs to be controlled to strict standards, and agglomeration of the particles is effectively avoided. This allows for improved milling efficiency and reduced energy consumption for the wet milling process since the viscosity of the suspension is kept low, and further reduces the probability of agglomeration and therefore the probability of mill screen blockage.
[0027] The nanometer-scale particles according to the present disclosure can represent a variety of materials useful in a variety of industries. For example, particles that can be milled as described herein include inorganic and organic solids, minerals, ores, silica, diatomaceous earth, clays, organic and inorganic pigments, pharmaceutical materials, carbon black, paint additives, pigments, photographic materials, cosmetics, chemicals, metal powders useful as catalysts or supports, stationary phase particles useful for analytical and preparative chromatographic separation of chemical compounds, powdered toners, therapeutic or diagnostic imaging agents, pharmaceutical actives, drugs, plant and herbal extracts, medicines, prodrugs, pharmaceutical preparations, etc. As described in more detail below, in some embodiments, the method is used to prepare nanometer-scale particles for use in preparing electrochemical materials for energy storage devices, such as electrodes and separators.
[0028] According to the method of the present disclosure, it is possible to obtain a particle size of less than 1 micrometer, for example less than 800 nanometers (nm), or less than 500 nm (D 90 Nanoscale particles having an average particle size of about 5 micrometers, D, have been demonstrated. 90 When using input particles with an average particle size of about 100 nm to about 200 nm, 10 Average particle size, D of about 150 nm to about 250 nm 50 Average particle size, and D of about 250 nm to about 350 nm 90 Product particles are prepared having an average particle size (D) within the size ranges above, or between the size ranges above and about 100 micrometers or less (such as about 50 micrometers or less, or about 30 micrometers or less, or about 10 micrometers or less). 90 ) input size is expected to be applicable in most currently practiced industrial or commercial applications. Further details regarding the wet media milling process are provided below, along with the electrostatic steric dispersants used in the milling process. In particular, two embodiments of the mill are disclosed below in conjunction with Figure 3A (vertical wet media mill) and Figure 3B (horizontal media mill). (Wet media milling)
[0029] In wet milling processes, the repeated collisions of milling media with the solid particulate material being milled, i.e., the substrate being milled, result in repeated breakage of the substrate and concomitant reduction in substrate particle size. When wet media milling processes are used to reduce the size of the substrate particles, the process is often carried out in a mill that includes a milling chamber containing milling media, the solid material or substrate to be milled, and a liquid carrier in which the media and substrate are suspended. The contents of the milling chamber are stirred or agitated by an agitator that transfers mechanical action and energy to the milling media. The accelerated milling media collide with the substrate in crushing, spalling, breaking, or other substrate particle size reducing energetic collisions, reducing the size of the solid substrate material and causing an overall reduction in substrate particle size and an overall reduction in the substrate average or mean particle size distribution. Examples of suitable wet milling systems include ball mills, planetary ball mills, recirculating stirred media mills, basket stirred media mills, ultrasonic media mills, and the like.
[0030] Milling media are generally selected from a variety of dense and hard materials, such as sand, steel, silicon carbide, ceramics, zirconium silicate, zirconium oxide and yttrium oxide (e.g., yttria-stabilized zirconia), glass, alumina, titanium, and certain polymers, such as cross-linked polystyrene and methyl methacrylate. Media shape may vary depending on the application, but spherical ball-shaped or cylindrical beads are commonly used. In some embodiments, milling media can be of various sizes and size distributions, including large and smaller milling media particles. Suitable liquid carriers for the milling media and substrate include water, aqueous salt solutions, aqueous buffer solutions, organic solvents, such as ethanol, methanol, butanol, hexane, hydrocarbons, kerosene, PEG-containing water, glycols, toluene, petroleum-based solvents, mixtures of aromatic solvents such as xylene and toluene, heptane, and the like. Typically, the solvent will be selected based on the substrate (product) particles.
[0031] Wet media mills useful for reducing the particle size of solid substrates can operate in batch mode or in continuous or semi-continuous mode. Wet media mills operating in continuous mode can incorporate a separator or screen to retain milling media with the larger particles of the solid substrate being milled in the milling zone or chamber of the mill while allowing smaller particles of the substrate being milled, i.e., product substrate particles, to exit the milling chamber in either a recirculation or discontinuous pass mode. Recirculation can be in the form of a slurry, suspension, dispersion, or colloid of the substrate suspended in a fluid carrier phase that moves, for example, using a pump, from the milling chamber to a holding vessel and from there back to the milling chamber. Separators or screens can be located at the exit of the milling chamber and include, for example, rotating gap separators, screens, sieves, centrifugally assisted screens, and similar devices that physically restrict the passage of milling media from the mill. The milling media is retained because the dimensions of the milling media are larger than the dimensions of the openings through which the reduced-size substrate particles can pass.
[0032] FIG. 3A depicts an exemplary vertical wet media mill 15 configured for use in accordance with some embodiments of the present disclosure, with reference numbers corresponding to the following illustrated features: 10:Motor 11: Shaft 12:Entrance 13: Filling height 14: Agitator 15: Media Mill 16: Milling room 17: Secondary Screen 19: Exit Screen 20: Exit 31:Intake port 32: Holding tank 33: Piping system 34: Pump 35: Piping system
[0033] The exemplary wet media mill 15 will now be described according to its normal operation. In one embodiment, milling media (not shown) and a fluid carrier containing an electrostatic steric dispersant may be added to the milling chamber 16 of the media mill 15 through an inlet 12. (The electrostatic steric dispersant is described in more detail below.) During this filling of the media mill 15, an agitator 14 may optionally be in operation, and an outlet 20 may be open to allow fluid carrier to exit the media mill 15 or may be closed to contain the fluid carrier. Optionally, a secondary, larger screen 17 may be provided within the media mill 15 that includes openings through which the milling media may pass.
[0034] The milling chamber 16 can then be filled with the solid substrate to be milled and optionally additional fluid carrier (optionally including additional electrostatic steric dispersing agent). The milling chamber 16 can also be further filled with an antifoaming agent to prevent bubble formation during the milling process, as known in the art. In embodiments, once all of the fluid carrier and substrate have been added, the slurry can have a solids content of about 5 wt% to about 40 wt%, such as about 10 wt% to about 40 wt%, or about 15 wt% to about 40 wt%, or about 20 wt% to about 40 wt%. The outlet 20 of the milling chamber 16 can then be closed and the media mill 15 can be filled to a height 13. Fluid carrier can be moved by pump 34 through inlet 31 to holding tank 32 using piping 35. The fluid carrier can be pumped from the holding tank 32 back to the inlet 12 of the media mill 15 via piping 33.
[0035] The contents of the media mill 15 are agitated or stirred by an agitator 14 driven by a motor 10 and coupled to a shaft 11, preferably at high speed or with high acceleration and deceleration. Agitation times to produce products according to the present disclosure can range from about 10 minutes to about 6,000 minutes or more, such as from about 10 minutes to about 3,000 minutes, or from about 10 minutes to about 1,000 minutes. The fluid carrier is continuously recirculated from the milling chamber 16 to a holding tank 32. This recirculation can be continued until a minimum or desired substrate particle size is obtained, such as a substrate particle size within the average particle size range described above. Additional electrostatic steric dispersant can be added as needed during this process.
[0036] At the end of the process, residual product particles of milled solid substrate remaining in the media can optionally be transferred under pressure or by pump 24 from the milling chamber 16 to the holding tank 32 as a dispersion in the fluid carrier. Essentially all of the milling media remains in the milling chamber 16, and the product substrate particles are isolated substantially free of milling media as a dispersion in the fluid carrier. The product substrate particles produced according to the present disclosure have a diameter of less than about 1 micrometer (D 90 ) particle size. The fluid carrier can be removed by drying or baking as known in the art. The steric dispersant may remain with the milled product after drying in some embodiments, while in other embodiments the steric dispersant may be removed, for example, by baking in a kiln. Removal of the steric dispersant will depend on the requirements of the final product and the intended use. In certain embodiments, as further described below, the dispersion of particles of the milled solid substrate in the fluid carrier product may be spray dried (e.g., by using high pressure air to force the droplets through a nozzle to form droplets, followed by heating the droplets) to isolate the nanoparticles as a dry powder.
[0037] FIG. 3B illustrates an alternative embodiment of an agitated media mill, a horizontal media mill. Many of the physical components of the embodiment of FIG. 3B are similar to the embodiment of FIG. 3A since both embodiments perform the same function. However, FIG. 3B focuses on specific functions occurring in each region of the mill with reference to functions (A) through (E) shown. As shown, in function (A), energy input to the mill through the shaft is dissipated in the suspension. In function (B), friction occurs in the suspension with an agitator near the chamber wall. In function (C), displacement occurs in the suspension while two or more grinding media approach each other. In function (D), the grinding media contact each other without causing stress to the suspended particles. Additionally, in function (E), the grinding media may temporarily deform after the contact. (Electrostatic steric dispersant)
[0038] Further details will now be provided regarding the electrostatic steric dispersants utilized in the wet media milling process of the present disclosure. The electrostatic steric dispersants provide electrostatic steric stabilization to the product particles. Electrostatic steric stabilization is a combination of electrostatic and steric stabilization. With reference to FIG. 4, electrostatic steric stabilization involves adsorbing a charged polymer (polyelectrolyte) onto the surface of the colloidal product particles. The surface of a particle is typically composed of negatively and positively charged sites. For example, such charged sites include, among others, OH - , H + , O2 - , and O - The relative concentration of each charge depends on several factors, including the nature of the particle, the oxidation state of the particle, and the pH of the system.
[0039] Polyelectrolytes have an overall electrical property associated with them (i.e., a positive or negative charge). Polyelectrolytes strongly adsorb to the surface of particles by attaching to oppositely charged sites on the surface of the particles. However, not all of the ionic sites on each polyelectrolyte are used in the adsorption process. Some of the ionic sites are used to adsorb the polyelectrolyte to the surface of the particle, while other ionic sites are on the part of the polymer that is free floating in the liquid medium. The combination of the same charges associated with the particle surface and the polymer chains in solution gives each particle an overall negative or positive charge relative to the particle-polymer composition. Each polymer-coated particle repels the same charges associated with other polymer-coated particles because such particles experience electronic repulsion. This electronic repulsion, combined with the steric effect of the polymer, disperses the product suspension. Furthermore, because both electrostatic and steric separation are obtained, particle separation is much stronger than either electrostatic or steric separation alone, less dispersant is required, and stringent control requirements for the amount of dispersant used in the milling process are relaxed.
[0040] Suitable polyelectrolytes for use according to the present disclosure as electrostatic steric dispersants include functional polymers having a number average molecular weight of at least about 500 g / mol, for example at least about 1,000 g / mol, such as at least about 2,000 g / mol. In some embodiments, the functional polymers can have a number average molecular weight as high as about 5,000,000 g / mol, or even as high as 50,000,000 g / mol. Typically, however, the number average molecular weight will be less than about 500,000 g / mol, such as less than about 100,000 g / mol, or less than about 50,000 g / mol, or less than about 25,000 g / mol. In particular, the polyelectrolyte dispersing agent can be selected from polymers and copolymers with charged or inorganic affinity groups, alkylammonium salts of polymers and copolymers, polymers and copolymers with acidic groups, functionalized comb copolymers and block copolymers, modified acrylate block copolymers, modified polyurethanes, modified and / or chlorinated polyamines, phosphate polyesters, polyethoxylates, polymers and copolymers with fatty acid radicals, modified polyacrylates such as transesterified polyacrylates, modified polyesters such as polyesters with acidic functional groups, polyphosphates, and mixtures thereof.Suitable electrostatic steric dispersing agents are sold, by way of non-limiting example, under the trade names Disperbyk-199 and Disperbyk-2010 (BYK GmbH, Wesel, Germany) and Flexisperse 225 and Flexisperse 300 (ICT, Cartersville, Georgia, USA). In embodiments, the product suspension in the wet media mill may have an electrostatic steric dispersant content of from about 2 wt % to about 20 wt %, such as from about 2 wt % to about 15 wt %, or from about 5 wt % to about 15 wt %, based on the weight of the solid particles. (Milling method)
[0041] Referring to FIG. 5, shown is a flow chart of a method 500 for producing nanometer-scale particles. The method 500 includes a premixing step 502, where a feed substrate suspension is premixed with a dispersant in a separate tank. The feed substrate suspension includes a liquid carrier medium and feed substrate particles. The liquid carrier medium can include water or an organic solvent. The feed substrate particles can include organic or inorganic solids, glass, graphene, metals, minerals, ores, silica, diatomaceous earth, clay, organic and inorganic pigments, pharmaceutical materials, or carbon black. The feed substrate particles can be present in the feed substrate suspension in an amount of about 5% to about 70% by weight, or about 5% to about 40% by weight of the feed substrate suspension. The electrostatic steric dispersant can be added in an amount of about 2% to about 20% by weight of the feed substrate particles. The electrostatic steric dispersant includes a polyelectrolyte. The polyelectrolyte can include a polymer or copolymer having charged functional groups or inorganic affinity groups.
[0042] The method 500 further includes step 504 of adding milling / grinding media to the mill, i.e., the mill is filled with an appropriate amount of milling / grinding media. Milling media are generally selected from a variety of dense and hard materials, such as sand, steel, silicon carbide, ceramics, zirconium silicate, zirconium oxide and yttrium oxide (e.g., yttria-stabilized zirconia), glass, alumina, titanium, and certain polymers, such as cross-linked polystyrene and methyl methacrylate. Media shapes may vary depending on the application, but spherical ball-shaped or cylindrical beads are commonly used. In some embodiments, milling media can be of various sizes and size distributions, including large and smaller milling media particles.
[0043] The method 500 further includes the step 506 of adding the premixed feed substrate suspension from step 502 to a media mill. The feed suspension can be added in a batch or continuous process. Optionally, a defoamer can also be added. Still further, the method 500 includes operating the media mill for a predetermined time to break down the feed substrate particles, thereby reducing the size of the feed substrate particles to less than about 1 micrometer, or less than about 800 nm, or less than about 500 nm, or less than about 400 nm (D 90 ) particle size. The predetermined time period can be from about 10 minutes to about 6,000 minutes, or from about 10 minutes to about 3,000 minutes, or from about 10 minutes to about 1,000 minutes. Additional electrostatic steric dispersant can be added during the predetermined time period that the media mill is operating.
[0044] The method 500 also includes a step 510 of recycling the nanometer-scale particles from the media mill for further grinding. Part of this step may further include removing the nanometer-scale particles from the media mill, which may include separating the nanometer-scale particles from the milling media. Optionally, the method 500 may include a step 512 of drying the nanometer-scale particles after removing the nanometer-scale particles from the media mill. Optionally, the method 500 may include a step 514 of separating the electrostatic steric dispersant from the nanometer-scale particles and removing any organics using a kiln after removing the nanometer-scale particles from the media mill. It should be understood that various steps in the method 500 may be repeated one or more times during operation of the method. (Energy storage materials)
[0045] As discussed above, in certain embodiments, the method prepares nanometer-scale particles for electrochemical materials, i.e., materials suitable for use in or as components of electrochemical devices (e.g., batteries, supercapacitors, etc.). In specific embodiments, the nanometer-scale particles for electrochemical materials are particularly useful in or as energy storage materials, such as electrodes (e.g., positive or negative electrodes). In such embodiments, an electrochemical feed substrate is utilized to prepare a feed substrate suspension in the method.
[0046] The electrochemical feed substrate is not particularly limited and may be or include any particulate material suitable for use in the methods of the embodiments described herein. More specifically, the electrochemical feed substrate may be any material suitable for use in the media mills of the present embodiments to prepare nanometer-scale particles. The nanometer-scale particles may subsequently be used to prepare components of an electrochemical device. For example, in some embodiments, the electrochemical feed substrate includes an energy storage material selected from anode active materials and cathode active materials (i.e., materials capable of functioning as anodes or cathodes, respectively), as described in further detail below. However, it will be understood that the electrochemical feed substrate may further include materials suitable for producing nanoparticles that can be utilized in components other than electrodes, such as separators, current collectors, and even multi-purpose composites.
[0047] With regard to suitable energy storage materials, those skilled in the art will readily understand that various precursor compounds may be employed in the preparation of electrodes, and that certain compounds and compositions may be used for the anode in some applications and the cathode in other applications. Thus, the specific materials described herein are not limited to a particular end use, unless otherwise specified. In general, suitable energy storage materials for the anode may be classified as intercalation-type anode materials (e.g., graphite, lithium titanate), alloy-type anode materials (e.g., compounds of silicon, tin, germanium, and antimony), or conversion-type anode materials (e.g., oxides, sulfides of transition metals, etc.). Thus, examples of specific anode active materials suitable for use in the method include carbon-based anode materials, such as those selected from graphite, graphene, activated carbon, pyrolytic carbon, hard carbon, and combinations thereof. Similarly, lithium titanate-based anode materials may also be utilized. Further examples include alloyed anode-type materials, such as those that include transition metal oxides, sulfides, nitrides, phosphides, fluorides, or combinations thereof. In another further embodiment, the energy storage material may include a silicon-based anode material, a tin-based anode material, a germanium-based anode material, an antimony-based anode material, an aluminum-based anode material, a magnesium-based anode material, or any combination thereof.
[0048] The energy storage material may include an active cathode material, which may be an inorganic active cathode material, an organic active cathode material, a polymeric active cathode material, or a combination thereof.
[0049] Examples of the positive electrode active material include positive electrode active materials selected from metal oxides, metal phosphates, metal silicides, metal selenides, transition metal sulfides, and combinations thereof. In general, suitable positive electrode energy storage materials can be classified as layered structure type positive electrode materials (e.g., graphite, lithium titanate), spinel structure type positive electrode materials, alloy type positive electrode materials (e.g., compounds of silicon, tin, germanium, and antimony), or conversion type positive electrode materials (e.g., transition metal oxides, sulfides, etc.). Polyanionic positive electrode compounds can also be used.
[0050] The energy storage material utilized in the method may be selected based on the type of energy storage device to be fabricated using or from the nanometer-scale particles. For example, Li-O2 batteries (also called lithium air batteries) may utilize carbon-based cathodes (e.g., activated carbon, carbon black, etc.) and may include or utilize precious metals (e.g., gold, silver, and palladium), non-precious metals (e.g., Ni / Ru particles, graphene-based Co / Cu bimetallic nanoparticles, etc.), transition metal oxides (e.g., Fe2O3, Fe3O4, NiO, CuO, Co3O4, etc.), and transition metal carbides (e.g., Mo2C), sulfides, and nitrides. Lithium-sulfur (Li-S) batteries typically utilize high-capacity sulfur (S, 1675 mAhg -1) positive electrode and lithium metal negative electrode. In such devices, lithium polysulfides are absorbed in metal oxides such as TiO2, MnO2, Nb2O5, Fe3O4, while lithium polysulfides are absorbed in metal sulfides such as Ni3S2, SnS2, FeS, CoS2, VS2, and TiS2. Both of these types of materials can be utilized in each of the present embodiments. For sodium-ion batteries, the negative electrode material is typically selected from graphite, hard carbon, soft carbon, titanium oxide, sodium titanate, and transition metal oxides, sulfides, nitrides, and phosphides of the general formula MaXb, where M is Fe, Co, Ni, Cu, and / or Mn, and X is O, N, F, S, Se, P, or H. Other materials include those where X is Si, Ge, Sn, Sb, or Bi. Other materials include cathode materials for zinc-ion batteries, such as MnO2, MnO, Mn2O3, Mn3O4, and ZMn2O4 based cathode materials, and cathode materials for zinc-air batteries, such as transition metal oxides, such as MnCo2O4, Co3O4 / MnCo2O4, Co3O4, NiCo2O4, or Fe3O4. Similarly, V2O5 and its derivatives can be used.
[0051] Again, regarding the method itself, reference is made to FIG. 7, which illustrates the respective method of this embodiment. Specifically, FIG. 7 illustrates a flow chart for method 600, which is a method for preparing nanometer-scale particles. The method 600 includes a premixing step 602, in which the feed substrate suspension (i.e., the electrochemically-fed substrate particles) is premixed with a dispersant in a separate tank. The electrochemically-fed substrate suspension includes a liquid carrier medium and feed substrate particles. The liquid carrier medium can include water or an organic solvent. The electrochemically-fed substrate particles typically include one of the energy storage materials described above, or other compounds for electrochemical use.
[0052] The method 600 further includes step 604 of adding milling / grinding media to the mill, as described above. In some embodiments, the milling media can be of various sizes and size distributions, including large milling media particles and smaller milling media particles. The method 600 further includes step 606 of adding the premixed feed substrate suspension from step 602 to a media mill. The feed suspension can be added in a batch or continuous process. Optionally, a defoamer can also be added. Still further, the method 600 includes operating the media mill for a period of time to break down the feed substrate particles, thereby reducing the size of the feed substrate particles to, for example, less than about 1 micrometer, or less than about 800 nm, or less than about 500 nm, or less than about 400 nm (D 90 ) particle size. Although not shown, the method 600 typically includes a step of recirculating the milled / unmilled feed substrate, e.g., by further grinding, to obtain nanometer-scale particles from the media mill. As with other embodiments described herein, part of this step can further include removing the nanometer-scale particles from the media mill, which can include separating the nanometer-scale particles from the milling media.
[0053] In certain embodiments, the method 600 includes a step 610 of drying the nanometer-scale particles after removing the nanometer-scale particles from the media mill. Typically, step 610 is performed by spray drying. For example, in some embodiments, the slurry obtained after the drinking process is pumped using high pressure air through a nozzle, which atomizes the liquid slurry into fine droplets. The droplets are then passed through a heating chamber where the liquid evaporates and forms a dry powder. The dry powder is then air pressure conveyed and collected in a centrifugal separator and / or bag filter. It will be appreciated that step 610 may be performed immediately after step 608, i.e., the wet slurry containing the now nanometer-scale particles may be introduced into the spray dryer immediately after the completion of milling.
[0054] Although not shown, it will be appreciated that the method can include a step of separating the electrostatic steric dispersant from the nanometer-scale particles and removing any organics after removing the nanometer-scale particles from the media mill. It will be appreciated that various steps in method 600 can be repeated one or more times during operation of the method.
[0055] The nanometer-scale particles prepared by the method may be used to fabricate electrochemical materials, whereby the electrochemical delivery substrate can be considered a precursor or intermediate in the fabrication of one or more electrochemical materials, for example, in certain embodiments, the nanometer-scale particles are used to fabricate electrodes.
[0056] It has been recently shown that by reducing the particle size of the solid electrolyte and increasing the particle size of the cathode active material, highly utilized cathodes with cathode active material loadings of over 50% by volume can be experimentally achieved, demonstrating that commercially suitable, high energy density cathode composites can be achieved by simple mixing and pressing methods. Furthermore, by using large cathode particles (≈12 μm) and small SE particles (≈1.5 μm), it has been shown that solid cathode composites with liquid-cell-level cathode volume loadings (≈50% by volume) can be prepared. In light of these findings, it will be appreciated that optimization of particle size in electrodes can enable commercially suitable cathode loadings. Furthermore, each nanometer-scale particle of the present embodiment is easy to press into electrodes (e.g., energy storage materials) by methods known to those skilled in the art. (Example)
[0057] The present disclosure will now be described by the following non-limiting examples. It should be noted that various changes and modifications can be applied to the following examples and procedures without departing from the scope of the present invention defined in the appended claims. Therefore, it should be noted that the following examples should be interpreted as merely illustrative and in no way as limiting. (Examples 1-5: Preparation of nanometer-scale particles)
[0058] Five different example particle suspensions were prepared containing water (as the liquid medium), crystalline silica / quartz particles or diatomaceous earth particles (as the solid substrate), antifoam agent, and various types and amounts of polyelectrolytes (as the electrostatic steric dispersant). The composition of each example slurry is provided in Table 1 below. [Table 1]
[0059] Each of the particle suspensions of the examples was placed in a recirculating stirred media mill (VMA Dispermat SL12 available from VMA-GETZMANN GmbH, Reichshof, Germany) that also contained yttria-stabilized zirconia (YSZ) beads as the grinding media. For each example, wet media milling was performed in the stirred media mill for a time period ranging from about 150 minutes to about 1,000 minutes. After the milling was completed, a nanoparticle analyzer (Anton-Paar Litesizer 500 available from Anton Paar GmbH, Graz, Austria) was used to measure the Dp of the particles. 10 , D 50 , and D. 90 The product particles were measured for average particle size, which is presented as a function of milling time for each of Examples 1 to 5 in Figures 6A to 6E, respectively. As shown in these figures, the method according to the present disclosure produced a D of about 100 nm to about 200 nm. 10 Average particle size, D of about 150 nm to about 250 nm 50 Average particle size, and D of about 250 nm to about 350 nm 90 The average particle size can be easily achieved.
[0060] Thus, the present disclosure has provided embodiments of a method and apparatus for producing nanometer-scale particles utilizing electrosterically stabilized slurries in a media mill. The method and apparatus advantageously maintain particle separation when particle sizes are below about 1 micrometer to avoid agglomeration and mill screen blockage. Moreover, the method and apparatus are beneficially suited for industrial-scale production in that they do not require strict control of any additives to prevent flocculation or viscosity spikes in the product suspension. (General Procedure for Preparation of Nanometer-Scale Particles for Energy Storage Devices)
[0061] To prepare the nanometer-scale particles, a feed material (e.g., quartz, diatomaceous earth, etc.) is combined with a solvent (e.g., water) along with a dispersant (e.g., Flexisperse 225 from ICT Chemicals) in a tank for 30-60 minutes. The resulting mixture is in the form of a slurry containing water and solids in the liquid.
[0062] The slurry is then continuously recirculated through the stirred media mill for a period of time. The stirred media mill is then filled with grinding media (Y-ZrO2 ceramic particles ranging in size from 0.05 mm to 10 mm). Only one size of media is used during the test run. For example, in a test run, 0.1 mm size media is filled into the mill chamber. A mixture of media sizes is generally not used in the stirred media milling process. The duration of the grinding is determined by the amount of mill power devoted to the grinding process.
[0063] After the milling process is complete, the slurry is pumped through a nozzle using high pressure air, which atomizes the liquid slurry into fine droplets. These droplets then pass through a heating chamber where the liquid evaporates to form a dry powder. The dry powder is then air-pressurized and collected in a centrifugal separator and / or bag filter. Examples 6-7: Preparation of nanometer-scale particles
[0064] Example 6: Initial particle size D 90 35 kg of Minusil-5 (crystalline quartz) with a diameter of 5 μm is mixed with 35 kg of water and 2.1 kg of Flexisperse 225 in a tank for 30 minutes. The mill is a Netzsch NEOS10 with a 10 L mill chamber and is filled with 27.83 kg of Y-Zr ceramic media with a size of 0.3 mm. The resulting slurry is then circulated in the mill for a total of 1380 minutes. The process consumed a total input power of 571 kWh. Figure 8A shows an SEM micrograph of the feed material Minusil-5.
[0065] Example 7: Initial particle size D90 25 kg of Silcosil-75 (crystalline quartz) with a diameter of 75 μm is mixed with 25 kg of water and 1.25 kg of Flexisperse 225 for 12 hours. The mill is a Netzsch NEOS10 with a 10 L mill chamber and is filled with 27.83 kg of Y-Zr ceramic media with a size of 0.3 mm. The slurry is then circulated through the mill for a total of 960 minutes. The process consumed a total input power of 404 kWh. Figure 8B is an SEM micrograph of the feed material Silcosil-75.
[0066] Figure 9 shows SEM micrographs of the agglomerates of nanometer-scale particles prepared in Examples 6-7 after spray drying. These round agglomerates are 5 μm to 50 μm in size and consist of primary nanoparticles. Figures 10A-10E show the agglomerates containing primary nanoparticles. These nanoparticles are about 100 nm to 200 nm in diameter.
[0067] It has been found that the method can easily mill 75 μm crystalline quartz to 100 nm. Quartz is a very hard material and is often difficult to process, but many of the battery precursor materials (commonly known as soft materials) can also be milled using the techniques of the present embodiments. Thus, the method provides a convenient means by which electrochemical materials, such as battery precursors, can be prepared from difficult to process materials.
[0068] While the above detailed description presents at least one exemplary embodiment, it should be understood that numerous variations exist. It should also be understood that the exemplary embodiment is merely an example, and is in no way intended to limit the scope, applicability, or configuration of the present invention. Rather, the above detailed description will provide those skilled in the art with a convenient guide for implementing an exemplary embodiment of the method and apparatus of the present invention. It is understood that various changes can be made in the function and arrangement of elements described in an exemplary embodiment without departing from the scope of the present invention as set forth in the appended claims. [Explanation of symbols]
[0069] 10:Motor 11: Shaft 12:Entrance 13: Filling height 14: Agitator 15: Media Mill 16: Milling room 17: Secondary Screen 19: Exit Screen 20: Exit 31:Intake port 32: Holding tank 33: Piping system 34: Pump 35: Piping system
Claims
1. 1. A method for preparing nanometer-scale particles for electrochemical materials, comprising: adding a feed substrate suspension to a media mill, the feed substrate suspension comprising a liquid carrier medium and electrochemically fed substrate particles; adding an electrostatic steric dispersant to the feed substrate suspension in the media mill, the electrostatic steric dispersant comprising a polyelectrolyte; The media mill is operated for a predetermined time to reduce the electrochemically fed substrate particles to a size of less than about 1 micron (D 90 ) forming nanometer-scale particles having a particle size; and recycling the nanometer-scale particles from the media mill for further grinding.
2. The method of claim 1 , wherein the liquid carrier medium comprises water or an organic solvent.
3. 10. The method of claim 1, wherein the electrochemical supply substrate comprises an energy storage material selected from an anode active material and a cathode active material.
4. 4. The method of claim 3, wherein the energy storage material comprises: (i) an intercalation type negative electrode material; (ii) an alloy type negative electrode material; (iii) a conversion type negative electrode material; or (iv) any combination of (i)-(iii).
5. 4. The method of claim 3, wherein the energy storage material comprises: (i) a carbon-based anode material selected from graphite, graphene, activated carbon, pyrolytic carbon, hard carbon, and combinations thereof; (ii) a lithium titanate-based anode material; or (iii) both (i) and (ii).
6. 4. The method of claim 3, wherein the energy storage material comprises an alloy anode material comprising a transition metal oxide, sulfide, nitride, phosphide, fluoride, or combinations thereof.
7. 4. The method of claim 3, wherein the energy storage material comprises: (i) a silicon-based anode material, (ii) a tin-based anode material, (iii) a germanium-based anode material, (iv) an antimony-based anode material, (v) an aluminum-based anode material, (vi) a magnesium-based anode material, or (vii) any combination of (i)-(vi).
8. 4. The method of claim 3, wherein the energy storage material comprises an inorganic active cathode material, an organic active cathode material, a polymeric active cathode material, or a combination thereof.
9. 4. The method of claim 3, wherein the energy storage material comprises a positive electrode active material selected from metal oxides, metal phosphates, metal silicides, metal selenides, transition metal sulfides, and combinations thereof.
10. 10. The method of claim 9, wherein the active cathode material comprises a layered structure type cathode compound, a spinel structure type cathode compound, an olivine type cathode compound, a polyanionic cathode compound, or a combination thereof.
11. The method of claim 1 , wherein the electrochemical delivery substrate comprises a separator material comprising an inorganic ceramic.
12. The method of claim 1 , wherein the polyelectrolyte of the electrostatic steric dispersant comprises a polymer or copolymer having charged functional groups or inorganic affinity groups.
13. 10. The method of claim 1, wherein the feed substrate suspension comprises, based on the total weight of the feed substrate suspension, (i) from about 5% to about 70% by weight of the electrochemically fed substrate particles, (ii) from about 2% to about 20% by weight of the electrostatic steric dispersant, or (iii) both (i) and (ii).
14. (i) the predetermined time is from about 10 minutes to about 6,000 minutes; or (ii) the nanometer-scale particles are 90 2. The method of claim 1, wherein (i) the particle size is less than about 500 nm; or (ii) both (i) and (ii).
15. The media mill includes milling media, 2. The method of claim 1, wherein recycling the nanometer-scale particles from the media mill for further grinding further comprises separating the nanometer-scale particles from the milling media.
16. 16. The method of claim 15, wherein (i) the milling media comprises one or more of sand, steel, silicon carbide, ceramics, zirconium silicate, zirconium and yttrium oxide, glass, alumina, titanium, cross-linked polystyrene, and methyl methacrylate; (ii) the milling media is provided in the shape of one or more of balls, beads, and cylinders; or (iii) both (i) and (ii).
17. 10. The method of claim 1, further comprising the step of drying the nanometer-scale particles after the step of recycling the nanometer-scale particles from the media mill for further grinding.
18. 20. The method of claim 17, wherein drying the nanometer-scale particles is performed by spray drying.
19. Further milling the nanometer-scale particles from the media mill to obtain a slurry; 20. The method of claim 18, wherein the slurry is directly subjected to the spray drying to obtain the nanometer-scale particles as a dry powder.
20. 13. An electrode comprising nanometer-scale particles prepared by the method of claim 1.
Citation Information
Patent Citations
Superfine particulate coal, superfine particulate coal-water slurry, production thereof, and composition using the same
JP1998077491A
Production of zirconia powder
JP1999057514A
finely ground particles
JP2004507343A
Electrolytic solution for metal air battery, and metal air battery using the same
JP2016076340A
Method for preparing a particulate cathode material
US20150158728A1